ARTIFICIAL INTELLIGENCE AND ITS INTEGRATION INTO TEACHING LEGAL ENGLISH - Mkrtchyan, Kristina; Mnatsakanyan, Lusine (Foreign Languages for Special Purposes, 2025)
The aim of this article is to study Artificial Intelligence in the context of teaching and learning. AI offers remarkable opportunities to enhance the teaching and learning of Legal English. The tools can help law students develop the linguistic competence and legal reasoning they need to thrive in a global legal environment. AI is revolutionizing not only how law is taught but also how specialized subjects like Legal English are delivered and understood. However, like in any other sphere, in legal and educational spheres as well, AI must be implemented thoughtfully and ethically, with full awareness of its capabilities and shortcomings.